CPAP by helmet for treatment of acute respiratory failure after pediatric liver transplantation. (24th November 2017) - Chiusolo, F.; Fanelli, V.; Ciofi degli Atti, M. L.; Conti, G.; Tortora, F.; Pariante, R.; Ravà, L.; Grimaldi, C.; de Ville de Goyet, J.; Picardo, S.
Abstract: ARF after pediatric liver transplantation accounts for high rate of morbidity and mortality associated with this procedure. The role of CPAP in postoperative period is still unknown. The aim of the study was to describe current practice and risk factors associated with the application of helmet CPAP. In this retrospective observational cohort study, 119 recipients were divided into two groups based on indication to CPAP after extubation. Perioperative variables were studied, and determinants of CPAP application were analyzed in a multivariate logistic model. Sixty patients (60/114) developed ARF and were included in the CPAP group. No differences were found between the two groups for primary disease, graft type, and blood product transfused. At multivariate analysis, weight <11 kg (OR = 2.9; 95% CI = 1.1‐7.3; P = .026), PaO2 /FiO2 <380 before extubation (OR = 5.4; 95% CI = 2.1‐13.6; P < .001), need of vasopressors (OR = 2.6; 95% CI = 1.1‐6.4; P = .038), and positive fluid balance >148 mL/kg (OR = 4.0; 95% CI = 1.6‐10.1; P = .004) were the main determinants of CPAP application. In the CPAP group, five patients (8.4%) needed reintubation. Pediatric liver recipients with lower weight, higher need of inotropes/vasopressors, higher positive fluid balance after surgery, and lower PaO2 /FiO2 before extubation were at higher odds of developing ARF needing CPAP application.